Residual limb fluid volume change and volume accommodation: Relationships to activity and self-report outcomes in people with trans-tibial amputation. (August 2018) - Sanders, Joan E; Youngblood, Robert T; Hafner, Brian J; Ciol, Marcia A; Allyn, Katheryn J; Gardner, David; Cagle, John C; Redd, Christian B; Dietrich, Colin R
Background: Fluctuations in limb volume degrade prosthesis fit and require users to accommodate changes using management strategies, such as donning and doffing prosthetic socks. Objectives: To examine how activities and self-report outcomes relate to daily changes in residual limb fluid volume and volume accommodation. Study design: Standardized, two-part laboratory protocol with an interim observational period. Methods: Participants were classified as "accommodators" or "non-accommodators, " based on self-report prosthetic sock use. Participants' residual limb fluid volume change was measured using a custom bioimpedance analyzer and a standardized in-laboratory activity protocol. Self-report health outcomes were assessed with the Socket Comfort Score and Prosthesis Evaluation Questionnaire. Activity was monitored while participants left the laboratory for at least 3 h. They then returned to repeat the bioimpedance test protocol. Results: Twenty-nine people were enrolled. Morning-to-afternoon percent limb fluid volume change per hour was not strongly correlated to percent time weight-bearing or to self-report outcomes. As a group, non-accommodators ( n  = 15) spent more time with their prosthesis doffed and reported better outcomes than accommodators. Conclusion: Factors other than time weight-bearing may contribute to morning-to-afternoon limb fluid volume changes and reported satisfaction with the prosthesis among trans-tibial prosthesis users. Temporary doffing may be a more effective and satisfying accommodation method than sock addition. Clinical relevance: Practitioners should be mindful that daily limb fluid volume change and prosthesis satisfaction are not dictated exclusively by activity. Temporarily doffing the prosthesis may slow daily limb fluid volume loss and should be investigated as an alternative strategy to sock addition.